2019
DOI: 10.2147/amep.s221256
|View full text |Cite
|
Sign up to set email alerts
|

<p>Case-Based Curriculum With Integrated Smartphone Applications Improves Internal Medicine Resident Knowledge Of Contraceptive Care</p>

Abstract: BackgroundContraception is an essential preventive service for all women. However, the literature suggests that internal medicine residents have low levels of confidence and knowledge of contraceptive care.ObjectiveWe designed and implemented a novel contraception curriculum promoting active, collaborative learning. We sought to evaluate whether this curriculum improved internal medicine resident knowledge of and comfort with contraceptive care through the administration of pre-/post-surveys.MethodsOur curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Differences in content testing results by subject matter in the present study align with our pilot study 16 and have been described in other medical specialties. 12,15 We hypothesize that in spite of a uniform curriculum development process, variation in curriculum efficacy may contribute to these findings. For example, a particularly effective esotropia traditional lecture may skew results in favor of the traditional lecture compared to the flipped-classroom format.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in content testing results by subject matter in the present study align with our pilot study 16 and have been described in other medical specialties. 12,15 We hypothesize that in spite of a uniform curriculum development process, variation in curriculum efficacy may contribute to these findings. For example, a particularly effective esotropia traditional lecture may skew results in favor of the traditional lecture compared to the flipped-classroom format.…”
Section: Discussionmentioning
confidence: 99%
“…The flipped classroom has had mixed but overall favorable outcomes in graduate medical education, including emergency medicine, [9][10][11] anesthesia, 12 critical care, 13 and internal medicine. 14,15 Greater exploration of the flipped-classroom approach in other graduate medical education specialties is needed.…”
mentioning
confidence: 99%
“…Another 2019 study evaluated internal medicine residents (n=38) who completed a contraception case-based assessment utilizing interactive online resources (CDC MEC and Reproductive Health Access Project websites) and smartphone applications (CDC Contraception and Contraception Point-of-Care applications). 25 The mean knowledge score improved significantly after this learning activity, nearly doubling from 49% correct answers on the pre-survey to 85% correct on the post-survey. Students were asked to rate their confidence and comfort level with counseling and assessing eligibility of contraception utilizing the following scale: (1 = very comfortable/confident, 5 = not at all comfortable/confident).…”
Section: Ongoing Contraceptionmentioning
confidence: 89%
“…When extrapolating data from other health professions similar barriers have been documented. [24][25][26][27][28] Barriers in delivering sexuality content, including contraception, within nursing contraceptive curricula have been documented and include: time constraints in the curriculum, less priority compared to other topics, comfort and capability to teach the topics, and importance not seen by faculty. 26,27 Aaberg found 40% of responding nursing programs identified time constraints as the primary barrier in 2016, which aligns with a study nearly 50 years prior in which 45% identified time as a barrier.…”
Section: Potential Barriers To Contraception Curricula Deliverymentioning
confidence: 99%